Enhancing livelihood security through the National Employment Guarantee Act: toward effective implementation of the act - Indira Hirway (Levy Economics Institute of Bard College, 2006)
The National Rural Employment Guarantee Act of 2005 is a major development in the history of poverty reduction strategies and rural development policies in India. Though the successful passage of the Act is due to the long struggle by NGOs, academics, and some policymakers, its successful implementation is a much bigger challenge. Effective implementation of the Act requires that labor-intensive works be planned for the needy poor on a continuous basis; that the right kind of assets are undertaken to promote the development of the local/regional economy; and that the labor-absorbing capacity of the mainstream economy be raised and assets maintained well and used productively to generate benefits for the poor, as well as to promote pro-poor economy growth. The past experiences of wage employment programs in India, however, suggest that there are several challenges ahead. These include strengthening the planning component of the program, particularly planning for infrastructure and natural resource management; coordination and conversion of the Employment Guarantee Scheme with ongoing programs; ensuring supply of labor on EGS works; promoting equity in the ownership of the assets; and using assets to improve the employment generation in the long run. This paper discusses these challenges and observes that the Employment Guarantee Act should not be treated as one more poverty alleviation program, but should be seen as an opportunity to eradicate the worst kind of poverty and to empower the poor and promote pro-poor growth of the Indian economy.
Keywords: J21; J31; O15; O20; O53; 330; Employment Guarantee Act and Employment Guarantee Scheme; Infrastructure Planning; Sustainable Livelihood; Planning for Natural Resource Management; Maintenance and Use of Assets Monitoring and Evaluation; Capacity Building